China National Medical Products Administration approval summary: anlotinib for the treatment of advanced non‐small cell lung cancer after two lines of chemotherapy. Issue 1 (20th June 2019) - Zhou, Ming; Chen, Xiaoyuan; Zhang, Hong; Xia, Lin; Tong, Xin; Zou, Limin; Hao, Ruimin; Pan, Jianhong; Zhao, Xiao; Chen, Dongmei; Song, Yuanyuan; Qi, Yueli; et al.
Abstract: Background: On May 8, 2018, the China National Medical Products Administration (NMPA) approved anlotinib, an orally administered anti‐angiogenesis inhibitor, for the treatment of patients with advanced non‐small cell lung cancer (NSCLC) who have progressed after treatment with two or more lines of prior systemic chemotherapy. Main body of the abstract: China NMPA reviewed and inspected a regional double‐blinded, placebo‐controlled, Phase III trial comparing the overall survival (OS) of NSCLC patients between the anlotinib and placebo arms. A total of 437 patients were randomized (2:1) to receive either anlotinib ( n = 294) or placebo ( n = 143) once daily on a 2‐week on and 1‐week off schedule. Patients with epidermal growth factor receptor ( EGFR ) or activating anaplastic lymphoma kinase ( ALK ) genomic tumor aberrations should have disease progression on NMPA‐approved therapy. Anlotinib is the first NMPA‐approved drug for patients with advanced NSCLC who have progressed on at least two lines of prior systemic chemotherapies in China. The approval was based on a statistically and clinically significant improvement in median OS with anlotinib (9.46 months) compared with placebo [6.37 months; hazard ratio (HR]) = 0.70, 95% confidence interval (CI) = 0.55–0.89; two‐sided log‐rank P = 0.002]. The confirmed objective response rate (ORR) was 9.2% in the anlotinib arm and 0.7% in the placebo arm. The median duration of response (DoR) was 4.83 months, with a 95% CI of 3.31–6.97 months. The toxicity profile of anlotinib was consistent with that of known anti‐angiogenesis inhibitors. Common adverse drug reactions (ADRs) in anlotinib‐treated patients included hypertension (67.4%), hand–foot syndrome (43.9%), hemoptysis (14.0%), thyroid stimulating hormone (TSH) elevation (46.6%), and corrected QT interval (QTc) prolongation (26.2%). Short conclusion: Anlotinib demonstrated a clinically significant OS prolongation as a novel therapeutic option for advanced or metastatic NSCLC following at least two lines of chemotherapy.